The Influence of Product Quality, Event Marketing, and Word-of-Mouth On Repurchase Intention Mediated by Purchase Decision - Timothy Jason Lianto; Eric Harianto (Dinasti Publisher, 2024)
The era of digitalization has brought significant changes to market dynamics, with consumers shifting towards edible consumer goods, especially healthier foods. In Indonesia, the FMCG (Fast Moving Consumer Goods) industry is experiencing rapid growth, driven by increasing consumer purchasing power, a large and diverse population, low product penetration, and rising health awareness. Cashew nuts have become one of the promising FMCG products due to their diverse nutritional value and benefits. Renjana Cashew was established as part of an entrepreneurship program at Ciputra University since 2021. Renjana products are roasted protein cashew nut snacks from Surabaya, featuring large-sized nuts, a crunchy texture, and unique flavors, making them suitable for everyday activities. This study aims to determine the effect of product quality, event marketing, and word of mouth on repurchase intention mediated by purchase decision. The research method used is quantitative descriptive confirmatory, with probability sampling technique using a simple random sampling approach. The sample size of this study is 318 respondents, who are customers of Renjana Cashew and have previously purchased the products. Data collection techniques involve using questionnaires and analysis with PLS-SEM. The results of the study indicate that product quality, event marketing, and word of mouth have a positive and significant effect on repurchase intention through purchase decision.